2021
DOI: 10.14245/ns.2040478.239
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Management of Iatrogenic Vertebral Artery Transection During Anterior Cervical Spine Surgery: A Case Report

Abstract: Anterior surgical approaches to the cervical spinal pathology have become a frequently used technique. Anterior cervical spine surgeries are generally considered to be safe with low incidence of neurological complications. Vertebral artery (VA) injuries are infrequent during an anterior cervical spine approach but can be devastating. A retrospective review of these injuries documents an incidence of 0.3%-0.5%. However, there is no established strategy or guidelines for managing iatrogenic VA injuries. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…However, iatrogenic VA injury is a rare complication of anterior approach cervical spine surgery [11]. Paghi et al reported VA injury at the same level as our report in a young male patient with cervical osteoblastoma who had undergone anterior approach cervical surgery [11]. Yunoki et al reported that repeated use of a spreader in two consecutive intervertebral space may have triggered VA occlusion after anterior cervical discectomy in a 50year-old patient [10].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, iatrogenic VA injury is a rare complication of anterior approach cervical spine surgery [11]. Paghi et al reported VA injury at the same level as our report in a young male patient with cervical osteoblastoma who had undergone anterior approach cervical surgery [11]. Yunoki et al reported that repeated use of a spreader in two consecutive intervertebral space may have triggered VA occlusion after anterior cervical discectomy in a 50year-old patient [10].…”
Section: Discussionsupporting
confidence: 67%
“…It is known that VA is vulnerable to injury and occlusion of VA can be seen as a result of cervical fracture and sharp head movements and can occur even with chiropractic manipulation [10]. However, iatrogenic VA injury is a rare complication of anterior approach cervical spine surgery [11]. Paghi et al reported VA injury at the same level as our report in a young male patient with cervical osteoblastoma who had undergone anterior approach cervical surgery [11].…”
Section: Discussionsupporting
confidence: 62%
“…Management consists intravenous heparin followed by oral oral anticoagualtion for all patients with acute dissections of the vertebral artery, regardless of the type of symptoms, unless there are contraindications such as the presence of a large infarct with associated mass effect, hemorrhagic transformation of the infarcted area, an intracranial aneurysm, and intracranial extension of the dissection with or without SAH [8].Endovascular therapy can be reserved for cases with recurrent neurological events despite on antithrombotics and who are all not a canditate for surgical therapy.Surgical therapy consists of insitu interposition of graft or extracranial intracranial bypass only for patients with persisting symptoms refractory to maximal non invasive management and who are not candidates for endovascular therapy.Continuation of anticoagulation therapy may be guided by MRA or ultrasound.Persisting irregularity or stenosis at 3rd month necessitates continuation of therapy for another 3 months. If features of stenosis persist beyond 6 months, it is advisable to shift the patient on antiplatelet agents [8,9]. Nearly 75% of patients make excellent recovery and overall death rate is less than 5%.Risk of spontaneous dissection approximates 2% in the first month and decreases to about 1% per year.Dissection usually does not recur in the same vascular territory [10].By conclusion we emphasise the clinical history elicitation of neck movement related trivial trauma are most important even without predisposing conditions for vertebral artery dissection in stroke management.…”
Section: Discussionmentioning
confidence: 99%
“… 30 37 46) Destructive intervention, complete occlusion of VA with coil has benefits in bleeding control, reduces recurrence and emboli, compared with other VA saving endovascular techniques. 37 43) However, insufficient blood flow of the contralateral VA can lead to ischemic strokes in brain stem and cerebellum. 44) Therefore, permanent VA occlusion with coil should be considered carefully to uncontrolled bleeding, in patients with tolerable collateral flow in posterior circulation and patent contralateral VA.…”
Section: Management Of Vai In Cervical Spine Surgeriesmentioning
confidence: 99%